Hydrophilic modification of PVDF-based SERS imprinted membrane for the selective detection of L-tyrosine. (15th February 2022) - Li, Hongji; Wang, Junfu; Fang, Haoqi; Xu, Hongda; Yu, Haochen; Zhou, Tianyu; Liu, Chunbo; Che, Guangbo; Wang, Dandan
Abstract: The polyvinylidene difluoride (PVDF) membrane has received considerable attention as a flexible surface enhanced Raman scattering (SERS) substrate due to its excellent mechanical and physicochemical properties. However, the poor fouling resistance of PVDF membrane due to its intrinsic hydrophobic property limits its practical application. To address this, in this investigation, a SERS imprinted membrane is synthesized based on W18 O49 /Ag composites. Firstly, to promote hydrophilicity, N-vinyl-2-pyrrolidone (NVP) and triethoxyvinylsilane (VTES) are copolymerized by hydrolysis condensation and linked with engineered polyvinypyrrolidone (PVP) chains exposed on the surface of membrane. Furthermore, W18 O49 /Ag composites are dispersed on the membrane under the assistance of polydopamine (pDA) to promote the pollution resistance. Subsequently, in order to demonstrate the practical detection property, W18 O49 /Ag/PVDF membrane is selected as the SERS substrate to synthesize SERS imprinted membrane by precipitation polymerization for the selective detection of L-tyrosine. The characteristic results reveal that the SERS-imprinted membrane exhibits satisfactory hydrophilicity, and it can effectively degrade the pollutant molecules absorbed on its surface under ultraviolet light illumination. It is proved from the detection results that the LOD of WADP-MIMs for L-tyrosine reached 10 −9 mol L −1 when the concentration of L-tyrosine changed between 10 −3 –10 −9 mol L −1 . The correlation coefficient (R 2 ) is 0.994 and the limit of detection is 10 −9 mol L −1 . Meanwhile, it can be applied for the selective detection of L-tyrosine in mixture samples. Overall, this study presents a novel approach for the hydrophilic modification and pollution resistance enhancement of PVDF-based SERS imprinted membrane, which can be effectively utilized for the selective detection of practical samples. Graphical abstract: Firstly, PVDF membrane was modified by hydrophilic procedure through copolymerization. Since the residual PVP chains were exposed on the surface of PVDF membrane, and the alkoxysilane segments could be linked with these chains by copolymerization. Subsequently, PVP was cross-linked with NVP and VTES through heat treatment under the protection of N2 . The membrane exhibited good hydrophilicity and acted as a secondary reaction platform for the detection of L-tyrosine. W18 O49 @Ag composites were modified on the PVDF membrane under the assistance of pDA, and the WADP-MIMs were prepared by precipitation polymerization. The WADP-MIMs exhibited sensitive SERS detection and self-cleaning properties, thereby improving the functionality of the SERS substrate. Image 1 Highlights: Promoting the hydrophilicity by the process of copolymerization. W18 O49 /Ag composites improve the detection sensitivity and pollution resistance. Improving the selective detection property by the process of imprinted polymerization.